The Effect of Parenting Program on Knowledge and Attitudes of Parents in Fulfillment The Basic Needs of Children in Karangtanjung Village - Masfa'if Riandi; Nashri Maulidah; Tria Mugi Safitri; Suhartono Suhartono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Giving a device to children who are too early is one example of parents' indifference to the child's development. This is due to the lack of knowledge and understanding of parents in educating and caring for children in the family. This study aims to analyze the effect of parenting programs on the knowledge and attitudes of parents in meeting the basic needs of children in Karangtanjung Village. This research is a descriptive study with the subject of research are 10 parents with different professional backgrounds in Karangtanjung Village. The research instrument used in the form of pretest and posttest questions, questionnaires, and interviews. The data analysis technique uses descriptive qualitative. The results showed that the existence of the Parenting Program can: (1) Increase parents 'knowledge of correct parenting according to the stage of child development, (2) Increase parents' concern for balanced nutrition which is important for children's growth and development. (3) Increase parents 'understanding of the importance of parents' participation in the child's learning process at home.